The impact of hypoxia and its modification of the outcome of radiotherapy - Horsman, Michael R.; Overgaard, Jens (Journal of radiation research, 2016)
Since the initial observations made at the beginning of the last century, it has been established that solid tumors contain regions of low oxygenation (hypoxia). Tumor cells can survive in these hypoxic conditions and are a major factor in tumor radioresistance. This significance has resulted in hypoxia becoming the most cited biological topic in translational radiation oncology. Identifying hypoxic cells in human tumors has become paramount, and the ability to do this has been improved by the help of new imaging techniques and the use of predictive gene profiles. Substantial data confirm the presence of hypoxia in many types of human tumors, although with considerable heterogeneity among individual tumors. Various approaches have been investigated for eliminating the hypoxic population. These include increasing oxygen availability, directly radiosensitizing or killing the hypoxic cells, indirectly affecting them by targeting the tumor vascular supply, increasing the radiation dose to this resistant population, or by using radiation with a high linear energy transfer, for which hypoxia is believed to be less of an issue. Many of these approaches have undergone controlled clinical trials during the last 50 years, and the results have shown that hypoxic radiation resistance can indeed be overcome. Thus, ample data exists to support a high level of evidence for the benefit of hypoxic modification. However, such hypoxic modification still has no impact on general clinical practice. In this review we summarize the biological rationale, and the current activities and trials, related to identifying and overcoming hypoxia in modern radiotherapy.